2021
DOI: 10.1038/s42003-021-01999-1
|View full text |Cite
|
Sign up to set email alerts
|

CryoET structures of immature HIV Gag reveal six-helix bundle

Abstract: Gag is the HIV structural precursor protein which is cleaved by viral protease to produce mature infectious viruses. Gag is a polyprotein composed of MA (matrix), CA (capsid), SP1, NC (nucleocapsid), SP2 and p6 domains. SP1, together with the last eight residues of CA, have been hypothesized to form a six-helix bundle responsible for the higher-order multimerization of Gag necessary for HIV particle assembly. However, the structure of the complete six-helix bundle has been elusive. Here, we determined the stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 59 publications
(60 reference statements)
0
29
0
Order By: Relevance
“…A similar density also was found in a sub-4 Angstrom structure of the immature CASP1 lattice obtained from an in vitro assembled, E. coli -expressed truncated Gag protein missing most of the MA domain (amino acids 16–99) [ 19 ]. Since E. coli does not contain IP6, and no additional IP6 was added to the assembly reaction, other molecules presumably also can be coordinated by the 12 lysines [ 26 ]. In any case, in the absence of a negatively charged molecule that neutralizes the two rings of twelve lysines, immature assembly appears not to occur.…”
Section: Immature Lentivirus Gag Assemblies Uniquely Coordinate Ip6mentioning
confidence: 99%
“…A similar density also was found in a sub-4 Angstrom structure of the immature CASP1 lattice obtained from an in vitro assembled, E. coli -expressed truncated Gag protein missing most of the MA domain (amino acids 16–99) [ 19 ]. Since E. coli does not contain IP6, and no additional IP6 was added to the assembly reaction, other molecules presumably also can be coordinated by the 12 lysines [ 26 ]. In any case, in the absence of a negatively charged molecule that neutralizes the two rings of twelve lysines, immature assembly appears not to occur.…”
Section: Immature Lentivirus Gag Assemblies Uniquely Coordinate Ip6mentioning
confidence: 99%
“…BVM acts to stabilize the six-helix bundle through direct binding to a central channel within the bundle [ 40 , 118 , 119 ]. Furthermore, a compensatory mutation for MI-dependent viral mutants, the SP1-T8I mutation, extends and stabilizes the six-helix bundle and allowed visualization of the bundle extending to the N-terminus of NC by cryo-ET [ 120 , 121 ]. Together, the studies with MIs have shown that the CA-SP1 region is a dynamic one, with an equilibrium between an unfolded or disordered structure and the rigid six-helix bundle.…”
Section: The Ca-sp1 Junction: a Key Molecular Switch Regulating Assem...mentioning
confidence: 99%
“…The non-canonical p8 domain in Murine Mammalian Tumor Virus (MMTV) Gag (Pr77 Gag ) and the p2 domain in FIV Gag (Pr50 Gag ) play a role in Gag-mediated assembly and particle production [56,57], while the p9 domain in Equine Infectious Anemia Virus (EIAV) Gag (Pr55 Gag ), the p2 domain in RSV Gag (Pr76 Gag ), the p6 domain in HIV-1 Gag (Pr55 Gag ), the pp24/pp18 domain in MPMV Gag (Pr78 Gag ) [58,59], and the pp21 domain in MTMV Gag contain common or alternative conserved motifs termed late domains (or L-domains), that specifically recruit the Endosomal Sorting Complex Required for Transport (ESCRT) machinery at viral budding sites to regulate viral budding of nascent virions at PM (Figure 1, for a review see [60]). Additional retroviral domains exhibit a structural role in viral assembly or in Gag multimerization, as, for instance, the p10 domain in RSV Gag [45], or the segment p2, located between NC and CA in HIV-1 Gag [61,62] as mutations in this domain modulate packaging of spliced viral RNAs [63,64]. Finally Gag domains can also exhibit regulatory functions as the p12 domain in MLV Gag (Pr65 Gag ) that, in its mature form, tethers the pre-integration complex (PIC) to host chromatin for integration [65], the PR domain in RSV Gag that displays an enzymatic protease activity, the p8 domain in MMTV Gag which is mono-ubiquitinated [30], and the p6 domain in HIV-1 Gag that was also observed to affect Gag binding to short oligoribonucleotides [66], and to regulate Gag binding specificity to gRNA fragments [67].…”
Section: Retroviral Gag Precursorsmentioning
confidence: 99%